Characterization of hydrochlorothiazide in solid formulations - De Salvi, Simone T. B. [UNESP]; Tita, Diego Luiz [UNESP]; Paiva-Santos, Carlos De O. [UNESP]; Antonio, Selma G. [UNESP] (Cambridge University Press (CUP), 2015)
Hydrochlorothiazide (HCTZ) is a diuretic used for the treatment of blood pressure (hypertension). HCTZ has two anhydrous polymorphs denoted as Forms I and II. Aiming at solid-state characterization, X-ray powder diffraction (XRPD) is known to be a powerful technique which has been successfully applied in investigating polymorphism in medicines. In this work, three tablets of HCTZ (a reference and two generic) were analyzed. The data were collected using Rigaku RINT2000 diffractometer copper rotate anode. The Rietveld method (RM) was applied for the characterization of HCTZ polymorphic form. For the crystalline excipients where the crystal structure is known, their phases were identified by the RM either. The results showed that all the tablets exhibit Form I of HCTZ, while the excipient lactose monohydrate is found to exhibit the crystalline form. One of the generics is also found to exhibit the excipient sodium lauryl sulfate (SLS) in the crystalline form. Therefore, the RM and XRPD are an efficient methodology for characterization of the crystalline Form I of the active principle of HCTZ and crystalline excipients lactose monohydrate and SLS in solid formulations. It is also interesting to observe excipients not described in the package insert of the medicament.
Keywords: Hydrochlorothiazide; polymorphism; Rietveld Method; X-ray powder diffraction